I survived the shark attacks of 1916 - Tarshis, Lauren (Tarshis, Lauren. I survived., 2010)
In July, 1916, Chet Roscow is fascinated by news accounts of the great white shark said to be attacking people along the New Jersey shore not far from his home, but when he goes swimming in Matawan Creek he discovers the truth of the stories.